The Relationship between Word Difficulty and Frequency: A Response to Hashimoto (2021). Issue 1 (1st January 2022) - Stewart, Jeffrey; Vitta, Joseph P.; Nicklin, Christopher; McLean, Stuart; Pinchbeck, Geoffrey G.; Kramer, Brandon
ABSTRACT: Hashimoto (2021) reported a correlation of −.50 ( r 2  = .25) between word frequency rank and difficulty, concluding the construct of modern vocabulary size tests is questionable. In this response we show that the relationship between frequency and difficulty is clear albeit non-linear and demonstrate that if a wider range of frequencies is tested and log transformations are applied, the correlation can approach .80. Finally, while we acknowledge the great promise of knowledge-based word lists, we note that a strong correlation between difficulty and frequency is not, in fact, the primary reason size tests are organized by frequency.